Pengaruh Proporsi Pati Bengkuang dan Tepung Kentang Terhadap Hasil Jadi Masker Perawatan Kulit Wajah - vitri amalia (Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang, 2018)
Facial skin problems such as blemishes, black spots, dull skin, premature aging and so on, require more optimal treatment, one of them using a mask Facial skin masks are one type of traditional cosmetics that can be used as a facial treatment to maintain the health of facial skin, namely by using yam starch and potato flour. The purpose of this study was to describe the various proportions of the results of the yam starch mask and potato flour with indicators of aroma, stickiness and panelist preference level and to analyze comparisons to assess the best proportion. This research is a research with true experimental method. The oup consisted of the results of the masked starch mask and potato flour with the proportion of 10g and 40g (X1), the proportion of 20g and 30g (X2) and the proportion of 30g and 20g (X3). The type of data used in this study is primary data. Data analysis techniques using ANOVA analysis and using Duncan's analysis as a further test. The results of the hypothesis test state that the price of F count> F table (27,271> 3,110) this proves that the hypothesis that reads